Myanmar's 'Rohingya' conflict - Ware, Anthony, 1966-; Laoutides, Costas (London : C. Hurst & Co. (Publishers) Ltd., 2018)
Exploring the long-running tripartite conflict between the Rohingya, Rakhine and Burman ethnic groups, this book offers a new analysis of the complexities of the conflict: the fears and motivations driving it and the competition to control historical representations and collective memory
Part I. Context : Personal journeys into this conflict : Complexities, misconceptions, and context
Recent violence and significance
Part II. Historical narratives, representation, and collective memory : History, memory, and the social psychology of conflict
: History, memory, and the social psychology of conflict : The Rohingya 'origin' narrative
Rakhine-Burman narratives:'Independence', 'unity', 'infiltration'
Part III. Conflict analysis : Philosophical landscape of conflict analysis theory : Security dilemma, minority complex, greed, and political economy
Identity and territory grievances in Rakhine state
The international community: Recommendations and conclusions.
Includes bibliographical references (pages 223-253) and index.
Refugee studies unit (RSU), CPJ.
R. K. Corporation
Keywords: Rohingya (Burmese people) -- Social conditions